Legal Assurance and Legal Protection in Land Registration in Indonesia - Suharyono Suharyono (Sriwijaya Law Review, 2019)
Legal assurance to protect the owner of the land title has been the main objectives of the 1997 Government Regulation No. 24. However, in reality, the objectives above cannot be spelled due to the negative publication system of land title registration regulated by the regulation above. The loophole the system has, inter alia, concerns with the actual or the correctness of land site or the physical data of the land.  As a result, a conflict will not be prevented between or amongst the true land deed holder, land rights holder and the third party. If the case is brought before the court, the further consequence is that the verdict will declare the cancelation of or invalidity of the land deed. Then the legal status of the land deed will become uncertain and landowners will lose their rights without getting any protection from the State.  The problem raised in this article regarding the negative system of land registration in the 1997 government regulation no. 24 does not provide legal protection for the landowner who has already land certificate. The results of the study showed that there were two different values of legal certainty and legal protection manifested in the Government Regulation No. 24 of 1997 and those of legal certainty and legal protection as mandated by the 1945 Constitution of the Republic of Indonesia.  Therefore it is not superfluous to state that legal certainty and legal protection are intended and regulated by Government Regulation No.24 of 1997 which is in contradictory to the manifested value of legal certainty and legal protection guaranteed by the 1945 Constitution